The politics of age and generation at the GAZE International LGBT Film Festival in Dublin. Issue 1 (January 2018) - Binnie, Jon; Klesse, Christian
Despite their global proliferation, queer film festivals, like film festivals more broadly, are somewhat understudied within the social sciences. This is despite scholarship within film studies that argues that they are significant sites of queer collectivity and sociality. This article examines queer film festivals as sites for the production of community and queer bonds. The authors argue that questions of age, temporality and intergenerationality are central to discourses of community mobilized by festival organizers. The article draws on empirical material from a qualitative study of the GAZE International LGBT Festival in Dublin – which formed part of a larger comparative study of the cultural activist politics of queer film festivals in Europe. Ken Plummer has argued for a greater appreciation of the role of time and generation within sexuality studies. Age, temporality and intergenerationality emerged as important issues within interviews conducted with organizers and volunteers at the festival. The analysis of these issues focuses on three key themes: (1) GAZE as a site of intergenerational community; (2) GAZE as a site of remembrance; and (3) demography and the sustainability of the festival. The article argues that the festival provides a distinctive site of intergenerational queer bonds; and that despite the creation of transnational spaces and discourses, references to the nation and national identity remain central to bonding experiences at the festival.